Marketing education at the University of Melbourne. Issue 1 (5th June 2017) - Ellis, Robert B.; Waller, David S.
Abstract : Purpose: The purpose of this paper is to analyse the early days of marketing education by observing the first "Marketing" subject in Australia, which was taught at the University of Melbourne, and comparing elements of the early subject to the introductory Marketing subject of today. Design/methodology/approach: The information used for this study was obtained from material in the University of Melbourne Archives, including calendar entries, subject descriptions, and university announcements, as well as from interviews and correspondence with various people including those in academic and administrative positions, and former students. Findings: The origins of university-level marketing education in Australia can be seen to have been shaped by several influences, including: the external environment of the country at that time; the areas of interest of academic staff; the availability of teaching material – textbooks, academic articles, appropriate case studies, academic research papers, etc.; the academic staff and teaching materials from the USA; and the extent to which the supporting technology of marketing had changed. Practical implications: By observing the development in marketing education over the years, from its beginnings in Australia at the University of Melbourne, this paper shows changes in the content which assists in the understanding of what has led to how marketing is taught in Australasian universities and colleges today. Originality/value: Marketing education research usually focusses on what is happening at the moment, so the value of this study is that it is one of the few that looks at marketing education from a historical perspective.